Investigation of Radioisotope count fluctuation and Shifts of Their Content Accumulation in Rock Minerals - Pasangka, Bartholomeus; Pasangka, Irvandi Gorby (Journal of Science and Science Education, 2024)
: The main problem studied in this study concerns the fluctuations in the number of radioisotopes and the shift in the center of their accumulation in rock minerals in Oesuu, Central Kupang after experiencing weathering a few years ago. The objectives of the study: determine the range of radioisotope counts in rock minerals in Oesuu Central Kupang after weathering several years ago, investigate the shift in the center of accumulation of radioisotope content in rock minerals in Oesuu Central Kupang by time-dependent radioisotope migration and decay processes. Research methods: observation, survey, mapping, analysis, and interpretation. Brief research procedures: Observations to determine the boundaries of the research site and create a grid, measure the background count around the survey location, measure the field data, correct the data, make three-dimensional curves and contours of the radioisotope radiation count, interpret and draw conclusions. Research result. The range of radioisotope radiation counts in rock minerals is 10 Counts per minute (cpm) to 107 cpm, and the results of the 2008 study were 9 cpm to 117 cpm. The distribution of the accumulation center of radioisotope content in rock minerals has shifted from the edge towards the center of the study site, which is most likely caused by radioisotope migration and accumulated by very strong cohesive forces between radioisotope elements contained in rock minerals.